Deuterium trapping by deformation-induced defects in tungsten. (13th September 2019) - Zibrov, M.; Balden, M.; Dickmann, M.; Dubinko, A.; Egger, W.; Mayer, M.; Terentyev, D.; Wirtz, M.
Abstract: The influence of defects induced by plastic deformation of tungsten (W) on deuterium (D) retention has been studied. Recrystallized W samples were subjected to tensile deformations at temperatures of 573 K and 873 K to strains in the range of 3%–38%. The dislocation density measured by transmission electron microscopy increased by about 40 times after deformation to the highest strain. The introduced defects were decorated with D by exposure to a low-flux D plasma at sample temperatures of 370 K and 450 K. D retention in the samples was studied using nuclear reaction analysis and thermal desorption spectroscopy. The trapped D concentrations after the plasma exposures were low (up to a few times 10 −4 at. fr.) and increased more slowly with strain than the dislocation density. Small vacancy-like defects and large vacancy clusters were detected in the samples by positron annihilation lifetime spectroscopy. Their concentrations also increased with strain more weakly than the dislocation density. It was concluded that these defects governed the D retention under plasma exposure at 450 K, while dislocations gave only a small contribution. It was also found that deformation already to the lowest strains significantly facilitates the formation of blister-like structures under D plasma exposure at 370 K. The defects associated with blister-like structures presumably gave a substantial contribution to D retention at 370 K.